Menelusuri Interaksi Antara Employee Engangement Pada Kepuasan Kerja Melalui Lensa Job Security: Sektor Pengajaran - Firman Fauzi; Sari Puspitarini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Examining employee engagement with a view to job satisfaction through mediated Job Security is the aim of this study. All respondent who have made worked from Senior High School and who meet the criteria listed constitute the population of this study. Purposive sampling was used to select 58 respondents. Data collection methods rely on survey methods, with research instruments in the form of a questionnaire. The statistical program was used for causal qualitative analysis. Employee Engagement (X1) and Job Security (X2), are variables exogen and endogen variable is job satisfaction (Y) to this study. This study uses Smartpls program to process and analyze data. The results showed that Employee Engagement had a positive and significant effect on Job Satisfaction, Job Security had a positive and significant effect on Job Satisfaction and Employee Engagement had a positive and significant effect on Job Satisfaction which was mediated by Job Security for the teaching staff.